2017
DOI: 10.31018/jans.v9i4.1478
|View full text |Cite
|
Sign up to set email alerts
|

Cone and seed maturity indices in Pinus wallichiana under temperate conditions of Kashmir Himalayas, India

Abstract: Pinus wallichiana (Blue pine) does not have a good seed every year and hence it becomes necessary to collect abundant quantity of seed during good seed year. It becomes necessary to know the exact time of seed ma-turity. To overcome this problem, the present investigation was conducted in Kashmir valley at four different altitudes and locations i.e. (1,600-2,000 masl–KFD), (2,000-2,400 masl -LFD), (2,400-2,800-PFD) and (2,800-3200 masl– SFD). The results revealed that seed collection clearly showed wide variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It was observed that under different treatments, their respective cone responses to the temperatures and subsequent seed germination varied across the species tested [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that under different treatments, their respective cone responses to the temperatures and subsequent seed germination varied across the species tested [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Bhat et al (2015) discovered that for Pinus wallichiana seed germination properties, a medium altitudinal range of 1600-2400 m asl is preferred. Similarly,Bhat et al (2018) discovered variations in germination percentage, germination value (GV), and mean germination time (MGT) for Abies pindrow at varied altitude gradients.…”
mentioning
confidence: 99%